2022
DOI: 10.4049/jimmunol.208.supp.55.10
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fuel choices control MAIT cell functions at homeostasis and after infection

Abstract: Mucosal-associated-invariant-T (MAIT) cells are an innate-like T cell subset that recognizes microbial-derived vitamin B metabolites. In contrast to conventional T cells, MAIT cells have an antigen-experienced phenotype and express memory markers by default. When activated, MAIT cells rapidly produce copious amounts of cytokines, resembling IFNg+ Th1- or IL-17+ Th17 effectors cells. While memory-like vs effector-like states in conventional CD4 and CD8 T cells are controlled by mutually exclusive metabolic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Furthermore, supplementation with the trichloroacetic acid metabolite α-ketoglutarate augmented human MAIT cell effector capacity ( 66 ), providing a further connection between metabolism and MAIT cell function. These data and other studies ( 57 ) suggest a causal link between metabolism and MAIT cell function.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, supplementation with the trichloroacetic acid metabolite α-ketoglutarate augmented human MAIT cell effector capacity ( 66 ), providing a further connection between metabolism and MAIT cell function. These data and other studies ( 57 ) suggest a causal link between metabolism and MAIT cell function.…”
Section: Discussionsupporting
confidence: 86%
“…S9B). KLRG1 + lung MAIT cells were virtually undetectable at steady state in C57BL/6 mice, but this was found to be a marker for memory-like MAIT1 cells in vaccinated mice ( 57 ). These data suggested that removal from SPF conditions decreased MAIT17 cells with perhaps an increase in MAIT1 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune responses are metabolically intense processes, with significant energy demands required to support de novo generation of biosynthetic intermediates 27 . The metabolic processes and nutrient requirements that govern MAIT cell effector responses are rapidly emerging but still incomplete 10,11,12,13,28 . Iron is an essential microelement and is critical for almost all living organisms, including humans and the majority of microbes 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have highlighted the importance of metabolism for MAIT cell functional responses 9 . Our group and others have demonstrated that MAIT cells are reliant on glycolysis to support their production of IFNg and Granzyme B 10,11,12 , whereas IL-17 production by MAIT cells has been linked to mitochondrial metabolism 13,14 . However, our knowledge of the nutritional requirements of MAIT cells remains limited.…”
Section: Introductionmentioning
confidence: 92%